The Grammatical Doctrine of Mohdhab al-Din al-Muhallabi (d. 583 AH): In his book “Nazm Al Fara’id” and “Hasir Al Shara’id” - Khalaf, Sundus Mohammed (Al-Adab Journal, 2022)
The use of the term in any of the sciences indicates the culture of that scholar, and his scientific knowledge of that science, and thus it is possible to identify his scientific doctrine to which he tends.I preferred to study his grammatical doctrine in his book “Nazm Al Fara’id”; To stand on his views and grammatical terms and controversial issues that he cited. His use of the visual term predominated on the Kufi. He used the term "Kufic" only, not BasriHe referred to the contentious issues in his book and mentioned in it the opinion of the Basrians and the Kufics without preference, from that: the issue of accusative of the present verb after waw, the morphing, and the advent of the broken (in) meaning (if), and the Hashaah being a letter and not a verb, as well as the addition of (what) with (if and where). ) And it became clear with the evidence from the books of grammarians that the increase (what) here is not a controversial issue between the Basrians and the Kufics, as he mentioned.It appears that Mohadhab al-Din was clearly influenced by the visual and kufic schools, and that was from his use of their terms and opinions, and he mentioned the controversial issues between them. It seems to me that he was more inclined to the Basri, and this appears from his mention of Sibawayh's opinions more than other scholars, and his use of the Basri term more than the Kufic term.Finally, I ask God for payment and integrity, and our last prayer is that praise be to God, Lord of the worlds